Operational scheduling of refined products pipeline networks with simultaneous batch injections - Cafaro, Diego Carlos (2010)
Petroleum refined products are mostly sent from oil refineries to distribution depots by trunk pipelines. Pipeline networks usually involve multiple input and exit terminals, and even dual-purpose stations. Several pumping operations can be simultaneously performed at different sources. Most of the computational burden on the scheduling of multi-source pipeline networks comes from three operational tasks: pump sequencing, batch sizing, and batch allocation. Previous contributions applied discrete decomposition approaches performing such tasks through heuristic-based decisions. This paper introduces an MILP continuous formulation for the operational scheduling of unidirectional pipeline networks that allows simultaneous batch injections. The problem goal is to satisfy depot requirements at minimum total cost. The optimal schedule of pumping and delivery operations is established all at once. Results show that simultaneous batch injections lead to a better use of the pipeline transport capacity and a substantial reduction on the overall time needed to meet depot demands.